2011
DOI: 10.4269/ajtmh.2011.10-0398
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Lesions as a Sign of Cutaneous Dissemination of Visceral Leishmaniasis in a Human Immunodeficiency Virus–Positive Patient Simultaneously Infected by Two Viscerotropic Leishmania Species

Abstract: Leishmaniasis is considered an emerging opportunistic disease in human immunodeficiency virus (HIV)–infected patients who have considerably variable clinical presentation. We report a patient with visceral leishmaniasis who had unexpected clinical aspects (atypical cutaneous lesions appearing after long-term evidence of visceral parasites). The patient had hepatoesplenomegaly in the absence of fever, but was otherwise generally healthy. The HIV viral load was low despite severe immunossupression (low lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Our group has previously reported that diminished levels of cellular activation were stably maintained in a co-infected patient during the remission phase over a 12-month prospective follow-up period [20]. However, reactivation episodes were again marked by increased activation along with progressively lower levels of specific IFN- γ in response to parasite antigens [20]. Herein, a positive correlation between the number of relapses and the degree of cellular activation was observed in co-infected patients (p<0.05 and r = 0.80, data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously reported that diminished levels of cellular activation were stably maintained in a co-infected patient during the remission phase over a 12-month prospective follow-up period [20]. However, reactivation episodes were again marked by increased activation along with progressively lower levels of specific IFN- γ in response to parasite antigens [20]. Herein, a positive correlation between the number of relapses and the degree of cellular activation was observed in co-infected patients (p<0.05 and r = 0.80, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that such pathogenic features are similar between VL and HIV, these results reinforce the concept that VL may contribute to worsening the immunosuppression induced by HIV infection, accelerating progression to AIDS. In addition, the quality of the Leishmania -specific immune response may remain impaired in Leishmania /HIV patients receiving HAART due to reduced T cell proliferative capacity and deficient interferon (IFN)-γ production [19,20]. Consequently, this deficient parasite control may favor the spread of L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these are associated with impaired immune responses against the parasite. Visceral leishmaniasis in HIV-coinfected individuals can be caused by strains and species that normally cause cutaneous disease [53] and is associated with atypical disease manifestations, such as the presence of cutaneous lesions as well as visceral parasitemia [54].…”
Section: Host Determinants Of Visceral Leishmaniasismentioning
confidence: 99%
“…In recent years, the disease has spread to all regions and emerged in urban areas 2 . In Latin America, cutaneous manifestations in leishmaniasis are related to Leishmania from the subgenus Viannia 3 ; however, there are reports of cutaneous lesions similar to those observed in post-kala-azar dermal leishmaniasis (PKDL), caused by Leishmania infantum, mainly in human immunodeficiency virus (HIV)-infected patients 4,5 . In addition, L. infantum can cause atypical cutaneous leishmaniasis in Central America unrelated to VL 6 .…”
Section: Introductionmentioning
confidence: 99%